2015
DOI: 10.5152/dcbybd.2014.408
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Workforce in Critical Care Units in University and Private Hospitals in Turkey

Abstract: Amaç: Çalışma, Türkiye'deki üniversite ve özel yoğun bakım ünitelerinde hemşire iş gücü ile ilgili mevcut durumu ortaya koymak amacı ile yapıldı.Gereç ve Yöntemler: Tanımlayıcı tipteki çalışmaya, Türkiye'deki 144 yoğun bakım üni-tesinde görev yapan 1416 hemşirelik çalışanı alındı. Veriler posta yoluyla toplandı, analizinde tanımlayıcı istatistikler kullanıldı.Bulgular: Hemşirelik çalışanlarının %89,4'ü hemşiredir; %66'sı lisans, %0,5'i yüksek lisans mezunudur. Katılımcıların, %48,6'sı yoğun bakım ünitesine öze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 16 publications
0
15
0
4
Order By: Relevance
“…Studies of intensive care units revealed nurses' workloads were very high (Sevinç et al. ; Teixeira et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of intensive care units revealed nurses' workloads were very high (Sevinç et al. ; Teixeira et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to our survey data, needles were the leading medical instrument causing injuries (77.55%, n=38), which corroborates the results of other similar studies. The habit of needle recapping, patient density due to high birth rates in our region, difficulties with staff recruitment [16,17] , sudden reflex movements and agitation of patients during suturing, and inappropriate waste management can be cited as occupational factors leading to needle-stick injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate number of experienced ICU nurses is of quite importance in proper healthcare [11,12] . Inadequate nurse staffing and ICU nurses who do not have specialized knowledge and skills are associated with increased mortality [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate nurse staffing and ICU nurses who do not have specialized knowledge and skills are associated with increased mortality [11] . In a recent study involving 1416 nursing staff members in ICUs in 144 Turkish hospitals, 48.6% had not received any critical care-related training and 30.2% had worked in the ICU for 1 year or less [12] . Similarly, our study shows that almost ¼ of nurses working in level 3 ICUs had <1 year of experience.…”
Section: Discussionmentioning
confidence: 99%